Elaboração e aplicação de instrumento para avaliação da gestão contábil integrada nas dimensões econômica, ambiental e social: uma análise exploratória em empresas do setor sucroalcooleiro do estado de São Paulo. - Pereira, Maria Aparecida (2011)
According to the environmental problems of the XXI century, in others words, the externalities caused by the production process, it is necessary to restructure the development in a sustainable manner, in order to supply the current consumption needs without to compromise the sustainability of the eart planet in the future. The restructuring requires strategic posture of organizations beyond the vision of profitability, creating a liability for implementation of new management methods and productive processes. This paper aims to propose an assessment tool to analyze the placement of plants in operation in the sugar-alcohol sector State of São Paulo which refers to an organizational management directed towards sustainable development in the financial, environmental, technological and human dimensions. Given this scenario, which refers to the accounting aspects, it is checked that the information provided by traditional accounting does not include aspects related to the externalities caused by the business practices according to the investments that aim at sustainability. An Integrated Accounting Management will contribute to raise the investment returns earned by companies engaged in the context of environmental preservation, due to the difficulty of measuring environmental costs.